Harmine Alleviates Titanium Particle-Induced Inflammatory Bone Destruction by Immunomodulatory Effect on the Macrophage Polarization and Subsequent Osteogenic Differentiation - Wang, Liangliang; Wang, Qing; Wang, Wei; Ge, Gaoran; Xu, Nanwei; Zheng, Dong; Jiang, Shijie; Zhao, Gongyin; Xu, Yaozeng; Wang, Yuji; Zhu, Ruixia; Geng, Dechun (Frontiers in Immunology, 2021)
Peri-prosthetic osteolysis (PPO) and following aseptic loosening are regarded as the prime reason for implant failure after joint replacement. Increasing evidence indicated wear-debris-irritated inflammatory response and macrophage polarization state play an essential role in this osteolytic process. Harmine, a β-carboline alkaloid primitively extracted from the plant peganum harmala seeds, has been reported to have various pharmacological effects on monoamine oxidase action, insulin intake, vasodilatation and central nervous systems. However, the impact of harmine on debris-induced osteolysis has not been demonstrated, and whether harmine participates in regulating macrophage polarization and subsequent osteogenic differentiation in particle-irritated osteolysis remains unknown. In the present study, we investigated the effect of harmine on titanium (Ti) particle-induced osteolysis in vivo and in vitro. The results suggested harmine notably alleviated Ti particle-induced bone resorption in a murine PPO model. Harmine was also found to suppress the particle-induced inflammatory response and promote the polarization of macrophages from M1 phenotypes to M2 phenotypes in vivo and in vitro, which improved anti-inflammatory and bone-related cytokines levels. In the conditioned medium from Ti particle-stimulated murine macrophage RAW264.7 cells treated with harmine, the osteoblast differentiation ability of mouse pre-osteoblastic MC3T3-E1 cells was greatly increased. And we also provided evidences that the immunomodulatory capacity of harmine might be attributed to the inhibition of the c-Jun N-terminal kinase (JNK) signaling pathway in wear particle-treated macrophages. All the results strongly show that harmine might be a promising therapeutic agent to treat PPO.